2021
DOI: 10.1002/bem.22364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wi‐Fi Radiofrequency Radiation on Carbapenem‐Resistant Klebsiella pneumoniae

Abstract: The hazardous consequences of electromagnetic field (EMF) exposure represent a public health concern. Common sources of EMF include smartphones and wireless fidelity (Wi‐Fi). The aim of our study is to assess whether exposure to Wi‐Fi radiofrequency radiation influences the pathogenic traits of carbapenem‐resistant Klebsiella pneumoniae. The susceptibility to antibiotics was evaluated by the determination of minimum inhibitory concentrations (MIC). In this study, K. pneumoniae showed a non‐linear response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Previous studies (8) have shown that the biofilm was positive association with carbapenem-resistance and the morbidity / mortality of 80% of chronic infections (9), which imposed recurrent attacks and prolonged untreatable poor prognosis in CRKP-BSI patients. In K. pneumoniae, the biofilm formation was mediated by the fimbriae and polysaccharides (10). The mrkA gene encoded the major subunits of type 3 fimbriae with the function of binding to the extracellular matrix, that necessary for biofilm formation of K. pneumoniae (11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (8) have shown that the biofilm was positive association with carbapenem-resistance and the morbidity / mortality of 80% of chronic infections (9), which imposed recurrent attacks and prolonged untreatable poor prognosis in CRKP-BSI patients. In K. pneumoniae, the biofilm formation was mediated by the fimbriae and polysaccharides (10). The mrkA gene encoded the major subunits of type 3 fimbriae with the function of binding to the extracellular matrix, that necessary for biofilm formation of K. pneumoniae (11).…”
Section: Introductionmentioning
confidence: 99%